ANALISIS RISIKO PRODUKSI BABY BUNCIS PADA KELOMPOK TANI DI KABUPATEN BANDUNG BARAT - Nadira Desiana Shinta; Sulistyodewi Nur Wiyono (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
Lembang Sub-district, Bandung Barat Regency is an area in West Java that produced various kinds of vegetables. One of the commodities that have been marketed to modern and export markets are baby beans. In every production process there is always have a risk that can be hinder and harm the entrepreneur. This research aimed to analyze the risk that become a priority during the production process of baby beans in the Macakal Farmer Group Cibodas Village, Lembang Sub-district, Bandung Barat Regency by using House of Risk (HOR) method. The results showed the highest risk at farmer level caused by climate change and erratic weather with Aggregate Risk Potential is 3.060. While the highest risk at the warehouse level is caused by the late harvest time of farmers with Aggregate Risk Potential is 1.440.